2017
DOI: 10.1002/1873-3468.12917
|View full text |Cite
|
Sign up to set email alerts
|

Topological characterization of the mitochondrial phospholipid scramblase 3

Abstract: Scramblases redistribute phospholipids in biological membranes. Phospholipid scramblase 3 (PLSCR3), which is located in mitochondria, has been reported to be involved in cardiolipin distribution from the inner to the outer membrane, thus regulating cellular processes such as apoptosis or mitophagy. However, the localization and topology of this protein has not been convincingly addressed to support a role in intermembrane phospholipid transfer. Here, we studied PLSCR3 topology within mitochondria. We show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…How PLSCR3 could move cardiolipin from one of the leaflets in the inner mitochondrial membrane to one of the leaflets in the outer mitochondrial membrane remains unknown and has been questioned. 56 Gene ablation and structural studies have failed to provide a clear picture of the biological function of the PLSCR family of proteins. Plscr1 germline knockout mice exhibited no obvious phenotypic abnormality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…How PLSCR3 could move cardiolipin from one of the leaflets in the inner mitochondrial membrane to one of the leaflets in the outer mitochondrial membrane remains unknown and has been questioned. 56 Gene ablation and structural studies have failed to provide a clear picture of the biological function of the PLSCR family of proteins. Plscr1 germline knockout mice exhibited no obvious phenotypic abnormality.…”
Section: Discussionmentioning
confidence: 99%
“…How PLSCR3 could move cardiolipin from one of the leaflets in the inner mitochondrial membrane to one of the leaflets in the outer mitochondrial membrane remains unknown and has been questioned. 56…”
Section: Discussionmentioning
confidence: 99%
“…To gain insight into Scramb1 role in SD formation, we conducted structure-function studies. Most PLSCRs consist of an unstructured, poorly conserved, N-terminal prolinerich domain of variable length, followed by a globular, 12-stranded β-barrel domain, with a C-terminal hydrophobic α-helix suggested to be buried within the β-barrel central cavity [30,54,55]. We found that the proline-rich region of Drosophila Scramb1-A probably mediates its interaction with Pyd.…”
Section: Scramb1 Role In Membrane Remodeling During Sd Formationmentioning
confidence: 80%
“…For example, cardiolipin was shown to stimulate the GTPase activity of Drp1, thereby promoting mitochondrial fission 80 . Interestingly, our mitochondrial proteomics data indicates that Plscr3b 81 , which has been implicated in facilitating the transport of cardiolipin from the inner to the outer mitochondrial membrane, is upregulated during embryogenesis, making it an additional candidate for future functional studies.…”
Section: Discussionmentioning
confidence: 99%